On the topology of desingularizations of Calabi-Yau orbifolds - Joyce, D (1998)
Let X/G be a 3-dimensional Calabi-Yau orbifold with codimension 2 singularities. The topology of crepant resolutions of X/G is described by the McKay correspondence (Reid, Ito). We study Calabi-Yau 3-folds Y that arise by deforming the complex structure of X/G. The McKay correspondence does not hold for such Y. We describe the topology of Y using the `Weyl group' of the singular set of X/G. Even in simple examples, this can give many different ways to desingularize X/G. It would be interesting to interpret these results in String Theory, which should lead to a generalization of the idea of orbifold CFT, similar to the idea of `discrete torsion' (Vafa, Witten).